Orthodoxie, hétérodoxies et capitalismes contemporains - Robert Boyer (Revue de la Régulation)
What have been since the inter-war period the relations between theories, ideologies and economic policies? How can these three components define a shared orthodoxy between the economic and political fields. Two of these configurations are analyzed: the Keynesian interventionism and the laissez-faire claimed by neoliberalism. The articulation with polity is crucial because no economic policy derives mechanically from a theory because it is the expression of a socio-political compromise which varies in time and space. The resilience of neoliberalism can be explained by the abandonment of any general theory, which has proved to be erroneous, in favor of governmental techniques derived from applied economics. The various heterodoxies (Keynesian, Schumpeterian, Marxist, institutionalist, ecologist) struggle separately to conquer hegemony, whereas they should seek to define the common bases of a single alternative. The past does not fully illuminate the future: the crisis opened in 2008 is both a repetition of the past and a novelty. It means the limits of the renovation of the discipline by its mathematization after WWII and calls for an epistemological break in response to the transformations of contemporary capitalisms.